Climatology of sea breezes along the Red Sea coast of Saudi Arabia. (25th April 2018) - Khan, Basit; Abualnaja, Yasser; Al‐Subhi, Abdullah M.; Nellayaputhenpeedika, Mohammedali; Nellikkattu Thody, Manoj; Sturman, Andrew P.
Abstract : Long‐term near‐surface observations from five coastal stations, high‐resolution model data from Modern Era Retrospective‐Analysis for Research and Applications (MERRA) and high‐resolution daily sea surface temperature (SST) from National Ocean and Atmospheric Administration (NOAA) are used to investigate the climatology of sea breezes over the eastern side of the Red Sea region. Results show existence of separate sea breeze systems along different segments of the Red Sea coastline. Based on the physical character and synoptic influences, sea breezes in the Red Sea are broadly divided into three regions: the north and the middle Red Sea (NMRS), the Red Sea convergence zone (RSCZ) and the southern Red Sea (SRS) regions. On average, sea breezes developed on 67% of days of the 10‐year study period. Although sea breezes occur almost all year, this mesoscale phenomenon is most frequent from May to October (78% of the total sea breeze days). The sea breeze frequency increases from north to south (equatorwards), and sea breeze characteristics appear to vary both temporally and spatially. In addition to land–sea thermal differential, coastline shape, latitude and topography, the prevailing northwesterly at NMRS region, the convergence of northwesterly and southeasterly wind system at RSCZ region and the northeast and southwest monsoon at SRS region play an important role in defining the sea breeze characteristics over the Red Sea. Abstract : The Red Sea is a unique body of water. Its specific shape, size, orientation, location and geomorphology offers opportunities and challenges to the current scientific knowledge of the climate of enclosed/semi‐enclosed basins. This paper investigated the climatology of sea breezes on the eastern coast of the Red Sea. Analysis shows existence of separate sea breeze systems along different segments of the Red Sea coastline. The onset, cessation, duration, strength and landwards extent largely depend on the synoptic forcing and topography of the region.